Exploring the Relationship of Supplier-Manufacturer with Sourcing Project Success in Terms of Strategic Performance - Hassan, Mohamad Ghozali; Abdul Talib, Asmat Nizam; Abdullah, Rohani; Ismail, Mohd Azril (2013)
The purpose of the current study was to investigate the relationship between rela-tional-oriented exchange and outsourcing success of supplier-manufacturer rela-tionship within Malaysia. This study used the partial least squares (PLS) and struc-tural equation modeling (SEM) tool to test the hypotheses. The data was gath-ered from a postal survey of 865 electri-cal & electronics sub-sector, of which 216 respondents participated in this study. The result indicated that relational-oriented exchange was positively related to the outsourcing success. Implications of the findings are further elaborated